EXPERIMENTAL STUDY ON ENERGY CONSUMPTION OF TEMPERATURE CONTROL BY USING ON-OFF INTELLIGENT FUNCTION - Pongswatd, Sawai; Sopha, Watcharapon; Asadi, Farzin; Smerpitak, Krit; Thepmanee, Teerawat (My University, 2023)
In order to save electrical energy for on-off temperature control, a useful concept of on-off intelligent function to execute in a programmable logic controller (PLC) is presented. An implementation of PLC-based control system based on electric heating is also described as a case study to demonstrate the performance of the proposed function. IEC 61131-3-based ladder diagrams were created by using Studio 5000 software to run in the PLC modeled CompactLogix L30ER. Compared with the traditional on-off control action, the proposed on-off intelligent function can minimize energy consumption of a heater used in the implemented temperature control by 4.57%-6.65%.
Keywords: Energy consumption; Intelligent function; On-off control; Programmable logic controller; Temperature control